1998
DOI: 10.1023/a:1020588618496
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Using laser scanning confocal microscopy, our objective was to measure mitochondrial, nuclear, and cytosolic free ionized Ca2+ in adult rabbit cardiac myocytes loaded with Ca2+-indicating fluorophores. When myocytes were loaded with Fluo 3 at 37 degrees C, the fluorophore was loaded extensively into the cytosol and nucleus, but poorly into mitochondria, and Fluo 3 fluorescence transients after field stimulation were confined to the cytosol and nucleus. In contrast, after loading at 4 degrees C, Fluo 3 also ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Thus, it seems that the RaM mechanism may be a component of the physiological response to upstream Ca 2+ signaling. Supporting this view, many groups have observed mitochondria in situ exhibit RaM-like behavior when exposed to nM levels of Ca 2+ [15], [24], [33], [34].…”
Section: Introductionmentioning
confidence: 85%
“…Thus, it seems that the RaM mechanism may be a component of the physiological response to upstream Ca 2+ signaling. Supporting this view, many groups have observed mitochondria in situ exhibit RaM-like behavior when exposed to nM levels of Ca 2+ [15], [24], [33], [34].…”
Section: Introductionmentioning
confidence: 85%
“…Similarly, Ohata et al (1998) suggested that mitochondrial accumulation of Ca 2+ released from the cardiac SR could be mediated by the structural association between IMFM and the SR. The details of ultrastructural links, however, remain under investigation.…”
Section: Ultrastructural Basismentioning
confidence: 99%
“…Cardiac IMFMs have been isolated from a number of animal species (Hoppel et al, 1982; Matlib et al, 1978; McMillin-Wood et al, 1980; Ohata et al, 1998; Palmer et al, 1977; Weinstein et al, 1985, 1986). The abundance of fibrillar material in the heart, coupled with the tight packing of this mitochondria between the Z-disks make isolation of IMFMs very difficult.…”
Section: Ultrastructural Basismentioning
confidence: 99%
“…The challenge with these methods is to avoid contamination from dye in the cytosolic component when intact myocytes are employed. Several papers from the Lemasters group tackled this issue by using confocal microscopy in rabbit cardiac myocytes loaded with either fluo-3/AM[24, 25], rhod-2/AM-[26, 27] or indo-1/AM[25]. They argued that the high spatial resolution of the confocal permitted them to distinguish cytosolic and mitochondrial signals and they found that Ca 2+ signals arising from mitochondria (i.e., colocalizing with the ΔΨ m probe TMRE) had rapid kinetics almost identical to the cytosolic Ca 2+ transient (although the time resolution of the recordings was not sufficient to analyze the rising phase of the transients in detail).…”
Section: Point: Evidence In Favor Of Fast Mitochondrial Ca2+ Uptake Imentioning
confidence: 99%
“…They argued that the high spatial resolution of the confocal permitted them to distinguish cytosolic and mitochondrial signals and they found that Ca 2+ signals arising from mitochondria (i.e., colocalizing with the ΔΨ m probe TMRE) had rapid kinetics almost identical to the cytosolic Ca 2+ transient (although the time resolution of the recordings was not sufficient to analyze the rising phase of the transients in detail). β-Adrenergic stimulation increased amplitudes of both the cytosolic and mitochondrial Ca 2+ transients[24, 25]. Although it has been argued that this experimental design inadequately excludes contamination of the fluorescence signal from the cytosolic compartment[11], it was shown that the mCU-inhibitor ruthenium red preferentially inhibited the mitochondrial Ca 2+ signal without altering the cytoplasmic transient[26].…”
Section: Point: Evidence In Favor Of Fast Mitochondrial Ca2+ Uptake Imentioning
confidence: 99%